Higher sustained virological response rates at 12 weeks in HIV-HCV co-infection; a tertiary centre experience. Issue 2 (February 2020) - Carvalho, L; Pillai, S; Daniels, E; Sellers, P; Whyte, R; Eveson, L; Foxton, M; Nelson, M
Summary: Objectives: The advent of direct-acting antivirals (DAAs) has revealed high rates of sustained virological response at 12 weeks (SVR 12) in Hepatitis C (HCV) treatment. Since the introduction of DAAs, in our centre, 42% of patients treated for HCV are HIV co-infected. Our study aimed to identify the SVR 12 rates between this group and HCV mono-infected patients. Methods: Retrospective data analysis of HCV mono-infection and HIV-HCV co-infection patients between 1st July 2015 and 30th November 2018, who had a SVR at 12 weeks post treatment. Co-infected patients were only referred for HCV treatment if they had well controlled HIV. Patients treated with Pegylated Interferon and Ribavirin were excluded. Results: During this period, 724 patients were treated for HCV and had data on SVR 12. Of those, 303 (41.8%) were co-infected with HIV. The SVR 12 was achieved in 386 (91.6%) of the HIV negative patients and 288 (95%) of the HIV positive patients (χ²= 3.10 p  = 0.078). Cirrhotic patients had poorer SVR 12 in both groups (90% in co-infection and 88.4% in HCV mono-infection). Conclusions: Our results demonstrate a higher SVR 12 in co-infected patients compared to patients with HCV mono-infection. We hypothesise that adherence to HIV treatment could increase compliance and success of HCV treatment.